ANALISIS RELEVANSI RAHN DENGAN DINAMIKA PERIKATAN SYARIAH DI INDONESIA - Billah, Ana (LPPM STAI Muhammadiyah Probolinggo, 2024)
Rahn, or pawn in Arabic, is a financial transaction that involves the delivery of goods as collateral for financing facilities. In the context of Indonesian law, pawn is regulated as a legal right obtained by the debtor over movable assets. In the dynamics of obligations, especially in Indonesia, there are conventional and sharia pawn, with the existence of these differences, it certainly requires a comprehensive understanding of the dynamics of obligations in Indonesia about their differences and similarities. By using the literature research method (library research) which relies on data or information that exists in the literature such as journals, books, newspapers, and other documents. descriptive analysis is used in this study to explain in detail or describe the phenomenon that is happening or has happened. This method helps in understanding the concepts related to the analysis of amanah product financing at the sharia pawn unit and the relevance of rahn with the dynamics of sharia obligations in Indonesia. Rahn, or pawn, has an important role in providing guarantees for loans given, with sharia principles that must be obeyed. Sharia pawn aims to provide financing in accordance with sharia principles, such as the prohibition of riba (interest) and unethical business practices, as well as increasing financial inclusion in Indonesia. the difference between conventional and sharia pawn, including in terms of legal basis, pawn actors, agreement letters, pawn agreements, benefits of pawn recipients, capital rental rates, and handling of auction money. Although the concept and way of working of conventional and sharia pawn have similarities, there are also significant differences, especially in terms of the interest system that is not in accordance with sharia principles. sharia pawn has a strategic role in encouraging financial inclusion, economic growth, and increasing public awareness and understanding of sharia finance. By adhering to sharia principles, sharia pawn provides alternative financing that is in accordance with Islamic beliefs and values, thus providing a positive impact for the Indonesian people as a whole. Keywords: pawn or collateral,sharia pawn or rahn,conventional pawn,Dynamics of sharia agreements